Caffeine use in the 21st Century: Considerations for public health - Rutherfurd-Markwick KJ; Ali A (Jacobs Publishers)
Caffeine has been consumed for thousands of years, with the primary sources originally being tea leaves and coffee beans. However, over the past 120 years new caffeinated foods and beverages have been developed and marketed worldwide, which has led to an increase in caffeine consumption in both children and adults. Concomitant with the rise in caffeine consumption has been a rise in the number of caffeine-induced incidents leading to emergency room visits or calls to poison centres. The reasons for the increases in caffeine consumption and related health concerns are likely to be multi-factorial and include aspects such as the wide range of caffeine sources available, the variability in caffeine content between and within products, lack of knowledge by the consumer, compounded by the wide variety of reasons for its consumption. In addition, with the advent of caffeinated products such as energy drinks and ready-to-drink beverages which frequently contain high levels of sugar, alcohol or other stimulatory compounds, adjuvant effects are possible. Life in the 21st century is faster and more competitive than it has ever been, and lifestyles are constantly changing to reflect that. Although consumption of increasingly accessible caffeinated beverages may aid in achieving life’s goals, the question remains as to how this increased consumption may impact on health, particularly in the long term. The aim of this review is to explore the above issues in an effort to raise awareness and stimulate discussion as to future public health concerns.